Empowering Process of Marginalized Masculinity Toward Self-Reliance in Chugong’s Solo Leveling Novel - Mohammad Raihan Daffa Fadlillah; Imas Istiani (Universitas Islam Negeri Palopo, 2026)
Systemic discrimination in modern meritocratic societies often traps individuals at the bottom of the social hierarchy, resulting in a state of marginalized masculinity. Despite the immense popularity of Solo Leveling, academic discussions addressing the intersection of masculinity and empowerment within modern fantasy literature remain limited. Thus, this study aims to examine the process of empowerment of the marginalized male protagonist, Jinwoo Sung, toward absolute independence in Chugong’s novel Solo Leveling. Using a qualitative research design and a character analysis approach, textual data were analyzed using the concept of marginalized masculinity by Connell and Messerschmidt, Kabeer’s three-dimensional framework of empowerment (resources, agency, and achievement), and Emerson’s philosophy of self-reliance. The findings indicate that the protagonist begins with severe physical and economic marginalization within the rigid hunter ranking system. Subsequently, the empowerment process is systematically triggered through the acquisition of the anomalous “System” as an initial resource, followed by a psychological shift to mobilize strategic agency during life-threatening encounters. Ultimately, the protagonist achieves radical autonomy, manifested through the formation of his own independent force and his active resistance to elite institutions. This study concludes that Solo Leveling serves as a critique of the meritocracy system, while also demonstrating that modern fantasy literature can redefine empowerment not as integration into an oppressive hierarchy, but as the attainment of sovereign defiance.